A randomized controlled trial of brief Somatic Experiencing for chronic low back pain and comorbid post-traumatic stress disorder symptoms - Andersen, Tonny Elmose (Eur J Psychotraumatol, 2017)
Background: It is well documented that comorbid post-traumatic stress disorder (PTSD) in chronic pain is associated with a more severe symptom profile with respect to pain, disability and psychological distress. However, very few intervention studies exist targeting both PTSD and pain. The current study is the first randomized controlled trial evaluating the effect of the body-oriented trauma approach of Somatic Experiencing (SE) for comorbid PTSD and low back pain. Although the method is well recognized by clinicians and widely used, SE still needs to be tested in a randomized clinical trial in comparison with an active control group. Objective: The aim of the current study was to compare the effect of an SE intervention in addition to treatment-as-usual (TAU) for patients with chronic low back pain and comorbid PTSD compared to TAU alone. Method: The study was a two-group randomized controlled clinical trial. A cohort of patients (n = 1045) referred to a large Danish spine centre between February 2013 and October 2014 were screened for PTSD and randomized to either TAU (4–12 sessions of supervised exercises for low back pain) or TAU plus SE (6–12 sessions). In total, 91 patients fulfilled the inclusion criteria and volunteered to participate in the study. Treatment effects were evaluated by self-report questionnaires comparing baseline measures with 12-month follow-up measures. Results: The additional SE intervention significantly reduced the number of PTSD symptoms compared with TAU alone, corresponding to a large effect size. Also, fear of movement was significantly reduced (moderate effect size). Both groups achieved a large reduction in pain-catastrophizing, disability and pain. Conclusions: A brief additional SE intervention was found to have a significant effect on PTSD and fear of movement compared to TAU alone. However, the overall effect of SE was less than expected and the clinical importance of the effects can be questioned.